2012
DOI: 10.1016/j.biopsych.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dorsal Anterior Cingulate Cortical Activity During Emotional Regulation and Top-Down Attentional Control in Generalized Social Phobia, Generalized Anxiety Disorder, and Comorbid Generalized Social Phobia/Generalized Anxiety Disorder

Abstract: Background Generalized Social Phobia (GSP) and Generalized Anxiety Disorder (GAD) are both associated with emotion dysregulation. In healthy subjects, research implicates dorsal anterior cingulate (dACC) in both explicit emotion regulation and top-down attentional control. While studies have examined these processes in GSP or GAD, no work compares findings across the two disorders. Moreover, no work examines functioning in cases comorbid for both disorders (GSP/GAD). Here we compare the neural correlates of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 48 publications
10
142
2
1
Order By: Relevance
“…CEM related dorsal mPFC responsivity may reflect a further increase in negative selfand other-referential processing in these individuals, since the mPFC is pivotal in self-referential processing [20,[48][49][50][51][52][53]. And a recent meta-analysis suggested that dorsal mPFC responsivity to social exclusion is related with enhanced social uncertainty, social distress, and social rumination [15].…”
Section: Discussionmentioning
confidence: 99%
“…CEM related dorsal mPFC responsivity may reflect a further increase in negative selfand other-referential processing in these individuals, since the mPFC is pivotal in self-referential processing [20,[48][49][50][51][52][53]. And a recent meta-analysis suggested that dorsal mPFC responsivity to social exclusion is related with enhanced social uncertainty, social distress, and social rumination [15].…”
Section: Discussionmentioning
confidence: 99%
“…Panic patients also displayed decreased activation in the left ventral ACC following successful CBT [70]. Patients with general social phobia and GAD show difficulties engaging dorsal ACC (dACC) during tasks requiring them to reappraise emotionally evocative images [86]. Although these results conflict with other findings of enhanced ACC activation, the authors note that this deactivation may reflect a reduced capacity to engage these regions as a function of task demands, i.e., reappraise the meaning of emotionally salient images [86].…”
Section: Prefrontal-amygdala Connectivity and Non-pathologicalmentioning
confidence: 98%
“…Aiming to compare GAD and social anxiety disorder (SAD) again (as did in the study from 2008 (Blair et al, 2008) and explore different cognitive tasks involved in emotion regulation, Blair et al evaluated explicit emotion regulation and top-down attentional control in these two groups of patients (Blair et al, 2012). These two cognitive functions are components of the emotional regulation process which are usually attributed to dorsal ACC.…”
Section: ) Studies Analyzing the "Emotional Dysregulation Model"mentioning
confidence: 99%